2022
DOI: 10.1093/nar/gkac769
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of branchpoint-distant exons is promoted by Cactin, Tls1 and the ubiquitin-fold-activated Sde2

Abstract: Intron diversity facilitates regulated gene expression and alternative splicing. Spliceosomes excise introns after recognizing their splicing signals: the 5′-splice site (5′ss), branchpoint (BP) and 3′-splice site (3′ss). The latter two signals are recognized by U2 small nuclear ribonucleoprotein (snRNP) and its accessory factors (U2AFs), but longer spacings between them result in weaker splicing. Here, we show that excision of introns with a BP-distant 3′ss (e.g. rap1 intron 2) requires the ubiquitin-fold-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Notably, silencing in these mutants remained largely unperturbed at CEN and MAT (Suppl. Figure S7c), corroborating previous findings demonstrating their intron-specific roles in splicing the shelterin components Rap1 and Poz1 (Anil et al, 2022; Thakran et al, 2018; Wang et al, 2014b). Cluster V was similarly deficient in SUBTEL and TEL silencing but also displayed defects at MAT .…”
Section: Resultssupporting
confidence: 91%
“…Notably, silencing in these mutants remained largely unperturbed at CEN and MAT (Suppl. Figure S7c), corroborating previous findings demonstrating their intron-specific roles in splicing the shelterin components Rap1 and Poz1 (Anil et al, 2022; Thakran et al, 2018; Wang et al, 2014b). Cluster V was similarly deficient in SUBTEL and TEL silencing but also displayed defects at MAT .…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, our previous studies on the interactomes of Gpl1, Gih35 and Wdr83 proteins identified Mtl1 and Ctr1 proteins of the MTREC complex, Nrl1 protein, as well as the intron-specific pre-mRNA splicing-ubiquitin fusion protein Sde2, to copurify as part of their interactomes [34,35]. This might suggest that the functions of the Gpl1-Gih35-Wdr83 complex are interconnected with the regulation of these proteins, either by regulating the Sde2 protein, which participates in the excision of introns [62,63], by participating in regulation of the Nrl1 protein, which suppresses accumulation of genome-threatening Rloop structures [13] or by modulating the function of proteins of the MTREC complex, which ensure the timely degradation of improperly spliced RNAs by the nonsense-mediated RNA decay (NMD) pathway [70,71]. To further support these hypotheses, additional studies investigating the interconnections between the Gpl1-Gih35-Wdr83 complex, other splicing factors and the proteins comprising the MTREC complex are warranted.…”
Section: Dysfunction Of the Gpl1-gih35-wdr83 Complex Affects The Spli...mentioning
confidence: 99%
“…Some human genes (>350) are conserved in S. pombe but absent from budding yeast, making S. pombe a powerful single-cell organism for the study of the related human gene functions. Recent examples where PomBase played a supporting role in the characterization of genes conserved in humans but absent in budding yeast include the identification of novel factors for mRNA splicing ( Anil et al . 2022 ; Selicky et al .…”
Section: Introductionmentioning
confidence: 99%